Contribution of bioacoustics for monitoring a discrete species : the Grey wolf (Canis lupus) - Papin, Morgane (CCSD, 2018)
The growing number of studies carried out in recent years has shown that bioacoustics is particularly interesting for the monitoring of secretive species. The emergence of autonomous recording devices, combined with new methods of analysis, have recently contributed to the increase of studies in this field. Over the last 30 years, many bioacoustic studies have been developed for the Grey wolf (Canis lupus), a secretive large carnivore known for its howls spreading over distances up to several kilometers. These researches notably aimed to improve its monitoring, which is complex because of the strong wolf dispersal capacities over long distances, the large extent of their territories and the various natural contexts in which they live. In this context, this PhD thesis was organized around three research axes. The first two axes focused on the contribution of passive bioacoustics for the Grey wolf monitoring in the field. By combining acoustic, statistical and cartographic analysis, the first objective was to develop a spatial sampling method adapted to large study areas for the detection of wolf howls by using autonomous recorders. Then, the same protocol was used to investigate the possibility to localize wolves thanks to their howls. Field experimentations, conducted in mid-mountain (Massif des Vosges) and lowland (Côtes de Meuse) environments, in two study areas of 30 km² and with an array of 20 autonomous recorders, demonstrated the high potential of passive bioacoustics for the Grey wolf monitoring. Indeed, nearly 70% of broadcasts (synthetic sound with similar acoustic properties to howls) were detected by at least one autonomous recorder in mid-mountain environment and more than 80% in lowland environment, for sound source-recorders distances of up to 2.7 km and 3.5 km respectively. By using statistical model and Geographic Information System, the detection probability of wolf howls was modeled in both study areas. In the mid-mountain environment, this detection probability was high or very high (greater ...